Evaluasi penggunaan antibiotik pada neonatus di NICU rumah sakit umum milik pemerintah daerah Banyumas - Dina Ratna Juwita; Diyas Hanifah Indrawati; Fazrin Nur Soleha; Irsalina Nurul Putri (Sasambo Journal of Pharmacy, 2023)
Infection is one of the leading causes of death in neonatal patients. One of the causes of these infectious diseases is bacteria, so antibiotics are the primary therapy in treating infections. The harmful effects of improper administration of antibiotics are pathogenic bacterial resistance, unwanted drug reactions, and inefficient treatment costs. The purpose of this study was to evaluate the quality of antibiotic use in neonatal patients treated in the Banyumas District Government Hospital NICU from December 2019 to March 2020 by using the Gyssens flow criteria and knowing the outcome of antibiotic use. This research is descriptive and observational. Data obtained from medical records and patient monitoring data with prospective data collection techniques. The inclusion criteria of this study were neonatal patients who were admitted to the NICU and received antibiotics for prophylactic and curative treatment. Total respondent for this study is 56 patients. The Gyssens flow criteria evaluation results were obtained from 53 medical records (94%)tegorized in category 0. There is one medical record each categorized in categories IV D (2%), IV B (2%), and III A (2%). Most of the use of antibiotics is rational. Antibiotics are not a determining factor for the outcome of patients with the same diagnosis and laboratory test results.